Mechanical properties of TI6AL4V open cellular structures for bone implants fabricated by selective laser melting process - Mohd Zaidi, Azir (2024)
Selective Laser Melting (SLM) has emerged as a pioneering additive manufacturing technique revolutionizing the fabrication of complex geometries with superior precision and mechanical properties. Unlike conventional manufacturing methods, SLM offers unparalleled flexibility in material design and customization, making it an ideal candidate to produce advanced engineering components, including biomedical implants. SLM operates through a process of fusing metal powders layer by layer using a powerful laser, following a digital model. This method enables the creation of intricate structures with customized microstructures, providing significant design flexibility and opportunities for functional optimization. Hip joint failure, attributed to degenerative ailments like osteoporosis and osteoarthritis, prompts Total Hip Arthroplasty/Replacement (THA) to alleviate pain and restore hip joint function. However, despite over three decades of refinement, premature loosening of the femoral stem persists due to stress shielding phenomena, arising from mechanical property mismatches between implants and surrounding bone. Traditional manufacturing techniques encounter challenges in producing titanium alloy open cellular structures with diverse designs, exacerbating stress shielding issues. This study investigates the impact of various strut sizes, shapes, and unit cell dimensions on the mechanical behavior of Ti6Al4V open cellular structures manufactured via the Selective Laser Melting (SLM) process. A substantial modulus mismatch between implants and surrounding bone leads to uneven stress distribution, bone resorption, heightened fracture risks, and implant loosening. Stress shielding, a biomechanical phenomenon, further exacerbates implant loosening by inducing adaptive changes in bone strength and stiffness. Traditional manufacturing methods struggle to produce titanium alloy open cellular structures with diverse design parameters, hindering advancements in implant technology. This research aims to evaluate the effects of different designs which are strut size, strut shape, and unit cell size on the mechanical behavior of Ti6Al4V open cellular structures under compressive loading. An optimal design characteristic for femoral implants was determined by assessing mechanical, physical, and biocompatibility properties as well as the optimum value of parameters to produce structures closely resembling human bone properties. The study involves fabricating Ti6Al4V open cellular structures via SLM, conducting compression tests on six groups of structures with varying porosity percentages by using Shimadzu Testing System VHS8800 to determine the young modulus value. Evaluation of surface roughness was done by 3D microscope, observing microstructures via optical microscopy, and assessing dimensional accuracy using CT scanning. Optimal parameters for Ti6Al4V open cellular structures include a unit cell size of 4x4x4, strut size of 0.7mm, hexagonal shape, and 91% porosity, approaching a modulus near 0.4GPa. This research contributes to orthopaedic implantology by elucidating strategies to mitigate stress shielding effects and improve long-term implant stability. This thesis thus contributes valuable insights that advance the current understanding of bone implantation, paving the way for further advancements in the field.